Noninvasive in vivo magnetic resonance measures of glutathione synthesis in human and rat liver as an oxidative stress biomarker. Issue 6 (25th April 2014) - Skamarauskas, John T.; Oakley, Fiona; Smith, Fiona E.; Bawn, Carlo; Dunn, Michael; Vidler, Daniel S.; Clemence, Matthew; Blain, Peter G.; Taylor, Roy; Gamcsik, Michael P.; Thelwall, Peter E.
<x xml:space="preserve">Abstract</x> Oxidative stress (OS) plays a central role in the progression of liver disease and in damage to liver by toxic xenobiotics. We have developed methods for noninvasive assessment of hepatic OS defenses by measuring flux through the glutathione (GSH) synthesis pathway. 13C‐labeled GSH is endogenously produced and detected by in vivo magnetic resonance after administration of [2‐13C]‐glycine. We report on a successful first‐ever human demonstration of this approach as well as preclinical studies demonstrating perturbed GSH metabolism in models of acute and chronic OS. Human studies employed oral administration of [2‐13C]‐glycine and 13C spectroscopy on a 3T clinical magnetic resonance (MR) imaging scanner and demonstrated detection and quantification of endogenously produced 13C‐GSH after labeled glycine ingestion. Plasma analysis demonstrated that glycine 13C fractional enrichment achieved steady state during the 6‐hour ingestion period. Mean rate of synthesis of hepatic 13C‐labeled GSH was 0.32 ± 0.18 mmole/kg/hour. Preclinical models of acute OS and nonalcoholic steatohepatitis (NASH) comprised CCl4‐treated and high‐fat, high‐carbohydrate diet‐fed Sprague‐Dawley rats, respectively, using intravenous administration of [2‐13C]‐glycine and observation of 13C‐label metabolism on a 7T preclinical MR system. Preclinical studies demonstrated a 54% elevation of GSH content and a 31% increase in flux through the GSH synthesis pathway at 12 hours after acute insult caused by CCl4 administration, as well as a 23% decrease in GSH content and evidence of early steatohepatitis in the model of NASH. Conclusion: Our data demonstrate in vivo13C‐labeling and detection of GSH as a biomarker of tissue OS defenses, detecting chronic and acute OS insults. The methods are applicable to clinical research studies of hepatic OS in disease states over time as well as monitoring effects of therapeutic interventions. (Hepatology 2014;59:2321–2330)